Reaction between Chalcones, 1,3-Dicarbonyl Compounds, and Elemental Sulfur: A One-Pot Three-Component Synthesis of Substituted Thiophenes - Adib, Mehdi; Rajai-Daryasarei, Saideh; Pashazadeh, Rahim; Jahani, Mehdi; Amanlou, Massoud (Synlett, 2018)
A simple and atom-economic synthesis of highly substituted thiophenes is demonstrated. Heating a solution of a chalcone and a linear/cyclic 1,3-dicarbonyl compound with elemental sulfur in CH3CN in the presence of NEt3 at 80 °C afforded the corresponding substituted thiophenes in good to excellent yields.
Keywords: multi-component reactions; substituted thiophenes; sulfur; chalcones; 1,3-dicarbonyl compounds